Land and Survey Department Samarahan / Nur Hidayah Jamail - Jamail, Nur Hidayah (University Technology MARA Sarawak, 2018)
Lots of individuals have contributed time, energy, ideas and suggestions during completing this practical report. I would like to thanks to Mr. Jim Carrey, the Administrative Assistant as well as the Head of Department of Administration n Land and Survey Department Samarahan for giving valuable opportunity for me to perform my practical training in Land and Survey Department Samarahan. I also want to thanks everyone in the department for giving me a valuable knowledge, guidance and valuable experience.